1997
DOI: 10.1146/annurev.anthro.26.1.385
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking in Men: The Anthropology of Masculinity

Abstract: Anthropology has always involved men talking to men about men, yet until fairly recently very few within the discipline had truly examined men as men. This chapter explores how anthropologists understand, utilize, and debate the category of masculinity by reviewing recent examinations of men as engendered and engendering subjects. Beginning with descriptions of four distinct ways in which masculinity is defined and treated in anthropology, special attention is paid to the relations of difference, inequality, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(72 citation statements)
references
References 63 publications
1
56
0
6
Order By: Relevance
“…The first, mainly anthropological, contests the Anglo‐ and Eurocentric linkage between friendship and heightened individualism and explores how practices of friendship are embedded in wider societal context (Bell and Coleman ; Desai and Killick ). Male social enclaves in particular have received rich ethnographic attention (Gutmann ), with studies that addressed distinct practices of friendship as varied as café sociability (Vale de Almeida ) or reciprocal animal theft (Herzfeld ). Second, political philosophers have debated the ways that interpersonal friendship can serve as a normative model for civic or national attachments in modern society (Schwarzenbach ; Yack ).…”
Section: The Private–public Divide In Studies Of Friendship and Solidmentioning
confidence: 99%
“…The first, mainly anthropological, contests the Anglo‐ and Eurocentric linkage between friendship and heightened individualism and explores how practices of friendship are embedded in wider societal context (Bell and Coleman ; Desai and Killick ). Male social enclaves in particular have received rich ethnographic attention (Gutmann ), with studies that addressed distinct practices of friendship as varied as café sociability (Vale de Almeida ) or reciprocal animal theft (Herzfeld ). Second, political philosophers have debated the ways that interpersonal friendship can serve as a normative model for civic or national attachments in modern society (Schwarzenbach ; Yack ).…”
Section: The Private–public Divide In Studies Of Friendship and Solidmentioning
confidence: 99%
“…Gutmann tells us that 'masculinities...have little meaning except in relation to women and female identities and practices' (Gutmann 1997). In the Diola case, giving birth marks full entrance into adult status for women, and men are not supposed to know anything about birth or women's reproduction.…”
Section: Boys Interrupted: Diola Male Personhood On the Body And In mentioning
confidence: 99%
“…Arkin and Dobrofsky (1978) argue that values related to ideals of sexual potency are intensified in the masculine environment of the army, especially in regard to training new recruits (e.g., in the Marines penis size is often directly linked to power). Gutmann (1997) notes that ethnographers have concluded that few men actually equate their manhood with their genitalia; nonetheless, studies indicate that they are a favorite point of reference. Consequently, in the IDF as well, there is a conspicuous rhetoric of sexual performance and genital size.…”
Section: The Right Sexualitymentioning
confidence: 99%